Assessment of cognitive impairment in patients with Parkinson's disease: prevalence and risk factors - Wang Q (Dove Medical Press, 2014)
Qiumei Wang,1 Zhenxin Zhang,2 Ling Li,2 Hongbo Wen,2 Qun Xu3,4 1Department of Geriatrics, 2Department of Neurology, 3School of Basic Medicine, Peking Union Medical College Hospital, 4Department of Epidemiology and Biostatistics, Institute of Basic Medical Sciences, Chinese Academy of Medical Sciences, Beijing, People's Republic of China Background: Although Parkinson's disease (PD) is clinically characterized by motor symptoms, cognitive impairment is one of the most disabling non-motor symptoms. Despite it attracting increasing attention worldwide, less is known about its prevalence in the Chinese population. The objective of this study was to assess cognitive impairment and related risk factors in Chinese PD patients. Methods: We collected the demographic, diagnostic, and treatment information of 901 PD patients from 42 centers throughout the People's Republic of China, then administered a battery of neuropsychological tests, to assess motor, cognitive, and neuropsychiatric symptoms. Results: Overall, 193 of 901 (21.4%) PD patients met the criteria for dementia (PD-D), and 206 (22.8%) met the criteria for mild cognitive impairment (PD-MCI). Visuospatial dysfunction and attention/executive impairment predominated. Increased severity of cognitive impairment was associated with greater motor impairment. Patients with psychiatric symptoms, such as depression and hallucinations, were more likely to have dementia. Potentially, the younger-aged and more educated are shown less cognitive impairment, but age at onset, and levodopa equivalent dose, were not associated with the presence of cognitive dysfunction. Conclusion: The prevalence and profile of cognitive impairment in Chinese PD patients, as well as the risk factors, are similar as those reported for other races, but the frequency of nonamnestic cognitive domains differs. Keywords: cognitive impairment, risk factor, prevalence, Parkinson's disease